1986
DOI: 10.1161/01.str.17.6.1102
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke depression: relationships to functional impairment, coping strategies, and rehabilitation outcome.

Abstract: SUMMARY This study examined the phenomenon of post-stroke depression and evaluated its impact on rehabilitation outcome. Sixty-four patients presenting to a rehabilitation program within weeks of first stroke were evaluated for depression through self-report measures and staff ratings. Patients also rated the particular coping strategies which they used in dealing with their illness and hospital stay. Physical and occupational therapists provided measures of functional impairment at admission and discharge. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
160
4
11

Year Published

1988
1988
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(184 citation statements)
references
References 23 publications
9
160
4
11
Order By: Relevance
“…There are between 1.6-2.0 million new stroke patients in China every year and post-stroke depression (PSD) is closely associated with the increased risk of mortality following a stroke (3). PSD negatively impacts upon subsequent rehabilitation; in a previous study by Sinyor et al, PSD patients demonstrated greater functional impairment than patients without depression, also scoring lower on behavioral action and functional status (4). The severity of depression is closely associated with health-associated quality of life and functional recovery in stroke survivors (5).…”
Section: Introductionmentioning
confidence: 99%
“…There are between 1.6-2.0 million new stroke patients in China every year and post-stroke depression (PSD) is closely associated with the increased risk of mortality following a stroke (3). PSD negatively impacts upon subsequent rehabilitation; in a previous study by Sinyor et al, PSD patients demonstrated greater functional impairment than patients without depression, also scoring lower on behavioral action and functional status (4). The severity of depression is closely associated with health-associated quality of life and functional recovery in stroke survivors (5).…”
Section: Introductionmentioning
confidence: 99%
“…A partir desses dados iniciais, vários estudos investigaram as taxas de prevalência da DPAVC que têm sido consideradas em torno de 23% a 60% 9,[14][15][16] . Nota-se que essa variação tem ocorrido em razão de fatores como: período pós-AVC no qual a avaliação foi realizada, definição (critérios) de depressão, tipo de assistência que os pacientes recebem, bem como a origem da população estudada (comunidade, hospitalar, centro de reabilitação e comunidade).…”
Section: Prevalência E Incidênciaunclassified
“…A DPAVC está associada a uma disfunção cognitiva e a um agravamento do comprometimento funcional e, quando a depressão é tratada adequadamente, ambos os prejuízos tendem a melhorar 3 . A manutenção da recuperação funcional dos pacientes com DPAVC, nos centros de reabilitação, tem menor duração do que os pacientes sem DPAVC após a alta 16 . Os pacientes com DPAVC têm maior período de permanência hospitalar e maior grau de comprometimento funcional 23 .…”
Section: Evolução E Prognósticounclassified
“…Embora em uma unidade de reabilitação os pacientes com depressão pós-AVC possam apresentar recuperação semelhante àqueles não deprimidos; com a alta, e sem a assistência hospitalar intensiva, os deprimidos tendem a apresentar significativa queda da recuperação funcional em comparação com os não deprimidos 41 . Pacientes com depressão no período agudo pós-AVC podem ter as atividades da vida diária comprometidas por até dois anos, independente das variáveis demográficas, do acesso aos serviços de saúde, do tratamento físico especializado, das características do AVC, do funcionamento social e do prejuízo cognitivo 42 .…”
Section: Impacto Da Depressãounclassified